Implementasi Pengelolaan Limbah Getah Karet: Analisis Siyasah Tanfidziyah terhadap Peraturan Pemerintah Nomor 22 Tahun 2021 tentang Penyelenggaraan Perlindungan dan Pengelolaan Lingkungan Hidup - Saputra Andiska (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the implementation of Article 274 of Government Regulation Number 22 of 2021 regarding rubber latex waste management in Rejosari Jaya Village and review it from the perspective of Siyāsah Tanfīdziyah. This field research with a qualitative approach shows that waste management is not yet optimal due to low public legal awareness, limited facilities, minimal socialization, and weak government supervision. From the perspective of Siyāsah Tanfīdziyah, the execution of executive functions has not been running optimally in terms of authority, oversight, and accountability. Therefore, improvements in guidance, supervision, and the provision of facilities are needed to achieve sustainable environmental management